Ethnic Variability in Glycemic Response to Sucrose and Isomaltulose - Tan, Wei Shuan Kimberly (Nutrients, 2017)
The aim of this study was to compare the glycemic response of Caucasians and Asians to two disaccharides of different glycemic index (GI), and to examine if ethnic groups that showed the largest glycemic response to sucrose would benefit the most when it is replaced with isomaltulose. Forty healthy participants (10 Chinese; 10 Malays; 10 Caucasians; and 10 Indians) consumed beverages containing 50 g of sucrose or isomaltulose on two separate occasions using a randomized crossover design. Capillary blood glucose was measured in a fasted state and at 15, 30, 45, 60, 90, and 120 min after beverage ingestion. Glycemic response to sucrose was significantly higher in Malays compared to Caucasians (p = 0.041), but did not differ between Caucasians vs. Chinese (p = 0.145) or vs. Indians (p = 0.661). When sucrose was replaced with isomaltulose, glycemic responses were significantly reduced in all ethnic groups, with the largest reduction in glycemic response being observed in Malays. Malays, who had the greatest glycemic response to sucrose, also showed the greatest improvement in glycemic response when sucrose was replaced with isomaltulose. This implies that Malays who are more susceptible to type 2 diabetes mellitus may benefit from strategies that replace high GI carbohydrate with lower GI alternatives to assist in glycemic control.